Consentement libre et éclairé et les stérilisations imposées de femmes des Premières Nations et Inuit au Québec - Commission de la santé et des services sociaux des Premières Nations du Québec et du Labrador; Basile, Suzie; Bouchard, Patricia (2022)
La présente recherche vise à pallier le manque de données sur la stérilisation imposée de femmes des Premières Nations et Inuit au Québec. Il s’agit d’une occasion unique pour les femmes des Premières Nations et Inuit au Québec de faire connaître leur histoire et de témoigner dans un cadre respectueux des principes de recherche avec les peuples autochtones (Asselin et Basile, 2012). À notre connaissance, aucune étude n’a encore été menée sur le sujet au Québec, si bien que ce projet semble tout à fait inédit et permet de répondre à un réel besoin de faire avancer la recherche sur cette problématique. Dans cette intention, la recherche sur la stérilisation imposée des femmes des Premières Nations et Inuit permet de mettre en lumière les enjeux sous-jacents de cette problématique. Ainsi, la notion de consentement libre et éclairé est au coeur de la recherche, tout comme l’étude du racisme et de la discrimination systémique vécue par les femmes autochtones au sein du système de santé.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; intersectionnalité; justice reproductive; maternité; pol4102; premier cycle; périodes historiques; québec; recherche avec les peuples autochtones; régions géographiques; santé; sciences humaines; sciences sociales; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; études autochtones

Challenging the “old boys club” in academia: Gender and geographic representation in editorial boards of journals publishing in environmental sciences and public health - Dada, Sara; van Daalen, Kim Robin; Barrios-Ruiz, Alanna; Wu, Kai-Ti; Desjardins, Aidan; Bryce-Alberti, Mayte; Castro-Varela, Alejandra; Khorsand, Parnian; Santamarta Zamorano, Ander; Jung, Laura; Malolos, Grace; Li, Jiaqi; et al. (PLOS Global Public Health, 2022)
In light of global environmental crises and the need for sustainable development, the fields of public health and environmental sciences have become increasingly interrelated. Both fields require interdisciplinary thinking and global solutions, which is largely directed by scientific progress documented in peer-reviewed journals. Journal editors play a critical role in coordinating and shaping what is accepted as scientific knowledge. Previous research has demonstrated a lack of diversity in the gender and geographic representation of editors across scientific disciplines. This study aimed to explore the diversity of journal editorial boards publishing in environmental science and public health. The Clarivate Journal Citation Reports database was used to identify journals classified as Public, Environmental, and Occupational (PEO) Health, Environmental Studies, or Environmental Sciences. Current EB members were identified from each journal’s publicly available website between 1 March and 31 May 2021. Individuals’ names, editorial board roles, institutional affiliations, geographic locations (city, country), and inferred gender were collected. Binomial 95% confidence intervals were calculated for the proportions of interest. Pearson correlations with false discovery rate adjustment were used to assess the correlation between journal-based indicators and editorial board characteristics. Linear regression and logistic regression models were fitted to further assess the relationship between gender presence, low- and middle-income country (LMIC) presence and several journal and editor-based indicators. After identifying 628 unique journals and excluding discontinued or unavailable journals, 615 journal editorial boards were included. In-depth analysis was conducted on 591 journals with complete gender and geographic data for their 27,772 editors. Overall, the majority of editors were men (65.9%), followed by women (32.9%) and non-binary/other gender minorities (0.05%). 75.5% journal editorial boards (n = 446) were composed of a majority of men (>55% men), whilst only 13.2% (n = 78) demonstrated gender parity (between 45–55% women/gender minorities). Journals categorized as PEO Health had the most gender diversity. Furthermore, 84% of editors (n = 23,280) were based in high-income countries and only 2.5% of journals (n = 15) demonstrated economic parity in their editorial boards (between 45–55% editors from LMICs). Geographically, the majority of editors’ institutions were based in the United Nations (UN) Western Europe and Other region (76.9%), with 35.2% of editors (n = 9,761) coming solely from the United States and 8.6% (n = 2,373) solely from the United Kingdom. None of the editors-in-chief and only 27 editors in total were women based in low-income countries. Through the examination of journal editorial boards, this study exposes the glaring lack of diversity in editorial boards in environmental science and public health, explores the power dynamics affecting the creation and dissemination of knowledge, and proposes concrete actions to remedy these structural inequities in order to inform more equitable, just and impactful knowledge creation.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; discipline; discours dominant; intersectionnalité; médecine; projet charge mentale; périodes historiques; racisme; santé; santé publique; sciences; sexisme; systèmes d'oppressions; thématiques

Better stories for a gender equal and fairer social recovery from outbreaks: learnings from the RESISTIRÉ project - Strid, Sofia; Schrodi, Colette; Cibin, Roberto (Gender & Development, 2022)
La pandémie a radicalement modifié l’organisation de la société, avec une augmentation du travail à domicile, de l’enseignement à domicile et de la présence en ligne, le tout avec des implications spécifiques (non)intentionnelles sur le travail de soins rémunéré et non rémunéré. Ces implications, comme celles d’autres crises, sont sexistes et se manifestent selon le sexe, l’âge, le handicap, l’origine ethnique/la race, le statut migratoire, la religion, la classe sociale et les intersections entre ces inégalités. Si de nombreuses études ont identifié ces impacts inégaux et négatifs et soulignent d’importantes inégalités liées aux soins, la contribution spécifique de cet article est différente, à savoir celle de mettre en évidence des pratiques inspirantes comme de meilleures histoires de et dans le domaine des soins pendant la pandémie. L’objectif est de rendre ces meilleures histoires visibles et de les considérer comme des moyens d’atténuer les impacts inégaux de la COVID-19 et de ses réponses politiques. Théoriquement, l’approche est basée sur les « meilleures histoires », telles que développées par Dina Georgis (2013, Better Story. Queer Affects from the Middle East , New York : State University). L'article utilise des données quantitatives et qualitatives, recueillies auprès des 27 États membres de l'UE, de l'Islande, de la Serbie, de la Turquie et du Royaume-Uni, dans le cadre du projet européen H2020 RESISTIRÉ.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; covid-19; europe; intersectionnalité; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travail du care

Les images de sensibilisation à la violence conjugale produites au Québec entre 1995 et 2021 : critique féministe de stratégies visuelles multiples - Yelle, Thérèse (Université du Québec à Montréal, 2022)
Dans ce projet, j’ai visé à (1) recenser les stratégies visuelles employées dans les campagnes de sensibilisation à la violence conjugale produites au Québec et à (2) établir les liens que ces stratégies entretiennent avec l'engagement féministe pris par le Gouvernement dans son Plan d'action gouvernemental en matière de violence conjugale de 1995. Dans un premier temps, à travers une étude visuelle multidisciplinaire, ancrée entre autres dans la rhétorique de l’image de Barthes (1964), mais aussi dans les théories du langage cinématographique (Edgar-Hunt, Rawle et Marland, 2011) et de l’art hypermédiatique (Lalonde, 2012), j’ai été amenée à constater la récurrence de stratégies visuelles visant à susciter des émotions fortes, comme la surprise, le choc, la colère ou la peur. Dans un deuxième temps, tout comme plusieurs auteur.trices de ma revue de littérature (West, 2013, Neal, 2015, Gabler, 2016, Goehring et al., 2017, Magaraggia et Cherubini, 2017, Wolf, 2018), j’ai remis en question la pertinence de ces stratégies dans le cadre d’une approche féministe de la violence conjugale. Pour ce faire, je me suis appuyée sur mon cadre théorique : les principes d’intervention féministes en violence conjugale. Il s’est dès lors avéré que beaucoup des images recensées contredisaient ces principes. Elles tendaient à retirer de l’agentivité aux victimes, à les revictimiser ou même à les culpabiliser. Je postule que cet état des lieux peut s’expliquer par le contexte sociopolitique et économique québécois des trente dernières années, contexte où les perspectives féministes n’ont jamais cessé d’être remises en question (Dupuis-Déri et Blais, 2015, Dupuis-Déri et Lamoureux, 2015) et où le néolibéralisme a mené à l’individualisation des problématiques sociales – entre autres (Flynn et al., 2018). Bien que ma recherche comporte ses limites, notamment car mon corpus exclut les nombreuses initiatives locales qui ont été créées, elle offre les bases d’un questionnement pertinent sur l’éthique de la fabrique des images de sensibilisation à la violence conjugale. Dans un travail ultérieur, la recherche pourrait comparer les initiatives gouvernementales aux initiatives locales, ou les initiatives du Gouvernement québécois aux initiatives d’autres gouvernements, comme celui d’Australie (campagne Respect). Il serait aussi pertinent de se questionner sur la place de ces images de sensibilisation dans un paysage médiatique et visuel où le sexisme ordinaire et les propos réactionnaires pullulent encore, malgré les avancées des dernières décennies (Cordelier et al., 2015, Lacasse et Charron, 2017). _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : image publicitaire; campagnes de sensibilisation; violence conjugale; images de la violence conjugale; lecture féministe de la violence conjugale; critique féministe de l’image; féminismes au Québec; antiféminismes au Québec.
https://uqam-bib.on.worldcat.org/oclc/1351471464
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; amériques; antiféminisme; approches et analyses; arts; biblioFem*; corps; discipline; genre; histoire de l'art; intersectionnalité; masculinisme; militance; mémoires/thèses; périodes historiques; québec; représentations médiatiques; ressource en ligne; régions géographiques; santé; thématiques; violences; violences conjugales

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Social vulnerability and the impact of policy responses to COVID‐19 on disabled people - Mladenov, Teodor; Brennan, Ciara Siobhan (Sociology of Health & Illness, 2021)
In this paper, we propose a conceptual framework for understanding the impact of the policy responses to COVID-19 on disabled people. These responses have overwhelmingly focused on individual vulnerability, which has been used as a justification for removing or restricting rights. This suggests the need to shift the attention towards the social determinants of disabled people's vulnerability. We do this by bringing literature on social vulnerability in disaster risk management or 'disaster studies' in contact with key concepts in disability studies such as the social model of disability, independent living, intersectionality, and biopower. Empirically, we draw on the findings of the global COVID-19 Disability Rights Monitor (www.covid-drm.org), as well as on reports from academic journals, civil society publications, and internet blogs. We put the proposed conceptual framework to work by developing a critical analysis of COVID-19 policies in three interrelated areas-institutional treatment and confinement of disabled people, intersectional harms, and access to health care. Our conclusion links this analysis with strategies to address disabled people's social vulnerability in post-pandemic reconstruction efforts. We make a case for policies that address the social, economic, and environmental conditions that disproportionately expose disabled people to natural disasters and hazards.
https://www.ncbi.nlm.nih.gov/pmc/articles/PMC8652534/
Keywords: approches et analyses; capacitisme; corps; covid-19; discipline; intersectionnalité; ressource en ligne; santé; sciences humaines; sociologie; soins de santé; systèmes d'oppressions; thématiques; vulnérabilité

The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Le texte Santinele Martino, A. et Fudge Schormans, A. (2021). Theoretical developments: Queer theory meets crip theory a été donné en lecture au cours SEX1920
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Guérison Collective Healing - Yuen, Felice; Gabriel, Wanda; Fast, Elizabeth (Guérison Collective Healing, 2021)
Aborder les expériences des femmes autochtones dans les prisons provinciales du Québec Vers une guérison collective Addressing the experiences of Indigenous women in Quebec’s provincial prison Towards Collective Healing
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; canada; communauté; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; militance; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système carcéral; système colonial; systèmes d'oppressions; thématiques; travail social; violences

Femmes et Environnement. Enjeux d'égalité pour toutes les femmes - Boivin, Martine (Le Réseau des Tables régionales de groupes de femmes du Québec, 2020)
Le Réseau des Tables régionales de groupes de femmes du Québec est un regroupement provincial composé des 17 Tables régionales de groupes de femmes au Québec. Il s’agit d’un regroupement féministe de défense collective des droits, qui travaille sur les questions mettant en jeu les intérêts et les droits des femmes. La spécificité du regroupement est représentée par l’expertise régionale développée par les Tables régionales dans les dossiers de la condition féminine. Porte-voix des régions auprès des instances nationales, le RTRGFQ favorise la prise de parole collective des Tables régionales, tout en respectant leurs particularités. Le RTRGFQ et les Tables régionales sont en action depuis plus de 20 ans pour favoriser la participation des femmes à la vie démocratique québécoise
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; charge mentale; charge émotionnelle; environnement; intersectionnalité; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; santé; thématiques

The work-life experiences of an invisible workforce: The case of live-in women migrant domestic workers in Malaysia - Wee Chan Au; Uracha Chatrakul Na Ayudhya; Tan, Yan Soon; Ahmed, Pervaiz K (Equality, Diversity and Inclusion: An International Journal, 2020)
Purpose>The purpose of this paper is to explore the work-life (WL) experiences of live-in women migrant domestic workers (MDWs), who represent a significant proportion of migrant workers globally. MDWs play a key role in enabling the work-life balance (WLB) of others, namely the middle-class households that employ them. Yet, their experiences have largely been invisible in mainstream WL literature. The authors draw on an intersectional approach to frame the WL experiences of this marginalized group of women at the intersection of being secondary labour segment workers, with significant legal and employment restrictions as migrant workers, who work and live in the same place as their employers.Design/methodology/approach>Qualitative interviews were conducted with 13 women MDWs from Indonesia and the Philippines working in Malaysia. The women talked about the meaning of work as MDWs, how they maintain familial connections whilst working abroad, and how they negotiate their WLB as live-in workers. Thematic analysis of the interviews focused on the intersection of the women’s multiple dimensions of disadvantage, including gender, class and temporary migrant-foreigner status, in shaping their accounts of the WL interface.Findings>Three thematic narratives highlight that any semblance of WLB in the MDWs’ lived experience has given way to the needs of their employers and to the imperative to earn an income for their families back home. The themes are: working as MDWs enables the women and their families back home to have a life; the co-existence of WL boundary segmentation and integration in relation to “real” and “temporary” families; and the notion of WLB being centred around the women’s ability to fulfil their multiple duties as MDWs and absent mothers/sisters/daughters.Research limitations/implications>The study is based on a small sample of live-in women MDWs in Malaysia, intended to promote typically excluded voices and not to provide generalizable findings. Accessing potential participants was a considerable challenge, given the vulnerable positions of women MDWs and the invisible nature of their work.Practical implications>Future research should adopt a multi-stakeholder approach to studying the WL experiences of women MDWs. In particular, links with non-governmental organizations who work directly with women MDWs should be established as a way of improving future participant access.Social implications>The study underscores the existence of policies and regulations that tolerate and uphold social inequalities that benefit primary labour segment workers to the detriment of secondary labour segment workers, including women MDWs.Originality/value>Extant WL literature is dominated by the experiences of “the ideal work-life balancers”, who tend to be white middle-class women, engaged in professional work. This study offers original contribution by giving voice to a taken-for-granted group of women migrant workers who make other people’s WLB possible. Moreover, the study challenges WL research by underscoring the power inequities that shape the participants’ marginal and disadvantaged lived experience of work, life, family and WLB.
Number: 5 Place: Birmingham Publisher: Emerald Group Publishing Limited
Keywords: 2000 à aujourd'hui; approches et analyses; asie; femmes migrantes*; femmes médecins; intersectionnalité; malaisie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travailleuses de la santé

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis